Strategic Strategic Digital Content and Brand Trust in Increasing Investment Interest in Futures Products at PT. Valbury Asia Futures Surabaya - Wardani, Putri Ayuning; Zawawi (LPPM Universitas Jambi, 2026)
The rapid advancement of digital technology has transformed the way investment companies communicate with potential investors through various digital platforms. In the futures investment industry, effective digital communication and public trust have become essential factors in attracting investment interest. Strategic digital content enables companies to deliver relevant and engaging information, while brand trust strengthens public confidence in investment services. This study aims to analyze the influence of strategic digital content and brand trust on investment interest in futures products at PT. Valbury Asia Futures Surabaya. This research employed a quantitative approach using a survey method involving 90 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The findings indicate that both strategic digital content and brand trust positively influence investment interest in futures products. The study concludes that companies can enhance public investment interest by developing effective digital content strategies while maintaining strong brand trust. These findings provide practical implications for investment companies in designing digital marketing strategies that encourage greater public participation in futures investment.